2019
DOI: 10.1038/s41598-019-42782-x
|View full text |Cite|
|
Sign up to set email alerts
|

KCC1 Activation protects Mice from the Development of Experimental Cerebral Malaria

Abstract: Plasmodium falciparum malaria causes half a million deaths per year, with up to 9% of this mortality caused by cerebral malaria (CM). One of the major processes contributing to the development of CM is an excess of host inflammatory cytokines. Recently K+ signaling has emerged as an important mediator of the inflammatory response to infection; we therefore investigated whether mice carrying an ENU induced activation of the electroneutral K+ channel KCC1 had an altered response to Plasmod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We have further shown that constitutively active KCC1 alters the inflammatory response to malaria infection in mice, and that this effect is associated with dramatically increased survival 27 . Here we sought to investigate whether the SPAK/OXSR1 pathway is involved in the host response to mycobacterial infection, and if this pathway could be manipulated as a hostdirected therapy against infection.…”
Section: Introductionmentioning
confidence: 67%
“…We have further shown that constitutively active KCC1 alters the inflammatory response to malaria infection in mice, and that this effect is associated with dramatically increased survival 27 . Here we sought to investigate whether the SPAK/OXSR1 pathway is involved in the host response to mycobacterial infection, and if this pathway could be manipulated as a hostdirected therapy against infection.…”
Section: Introductionmentioning
confidence: 67%
“…Indeed, a contemporary article has demonstrated WNK1 deficiency potentiates NLRP3 inflammasome activation in mice (Mayes-Hopfinger et al, 2021). We have further shown that constitutively active KCC1 alters the inflammatory response to malaria infection in mice, and that this effect is associated with dramatically increased survival (Hortle et al, 2019b). Here we sought to investigate whether the SPAK/OXSR1 pathway is involved in the host response to mycobacterial infection, and if this pathway could be manipulated as a host-directed therapy against infection.…”
Section: Introductionmentioning
confidence: 80%
“…The correlation between RBC dehydration and hemolysis in PIEZO E756del activated RBC suggests the following mechanism of protection of PIEZO1 E756del carriers from severe forms of malaria: gain of function PIEZO1 E756del becomes activated by shear stress and leads to increased RBC dehydration that, in turn, leads to increased RBC hemolysis and inefficient parasite replication. More generally, cell dehydration could emerge as a factor associated with the amelioration of malaria both in malaria patients and in rodent malaria models due to i) sickle hemoglobin, 30,31,45 ii) deficiency in PMCA4 production, 46 iii) gain of function KCC1 co-transporter 47-48 and iv) gain of function PIEZO1 E756del . 3,7 Further investigations into the protective mechanisms of erythrocyte dehydration and erythrocyte membrane pathology on malaria parasite biology and malaria pathogenesis is warranted.…”
Section: Discussionmentioning
confidence: 99%